2016
DOI: 10.1093/mnras/stw2690
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between star formation activity and galaxy structural properties in CANDELS and a semi-analytic model

Abstract: We study the correlation of galaxy structural properties with their location relative to the SFR-M * correlation, also known as the star formation "main sequence" (SFMS), in the CANDELS and GAMA surveys and in a semi-analytic model (SAM) of galaxy formation. We first study the distribution of median Sérsic index, effective radius, star formation rate (SFR) density and stellar mass density in the SFR-M * plane. We then define a redshift dependent main sequence and examine the medians of these quantities as a fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 132 publications
9
67
0
Order By: Relevance
“…This would imply that galaxy growth does not track the halo growth from z ∼ 2-0, so the galaxy size should be proportional to the halo's size at z ∼ 2. We find that a more detailed implementation of the standard adiabatic contraction model within a full semi-analytic merger tree model (including the effects of gas, disk instabilities, and mergers; Somerville et al in prep) produces disks that are about 50% too large at a given mass at z ∼ 0, compared with observations, but are in good agreement with the size-mass relation from CANDELS at 0.4 Brennan et al 2017). However, we do not support "pseudoevolution" as a complete explanation for two reasons.…”
Section: Theoretical Expectations For Disk Sizessupporting
confidence: 74%
See 1 more Smart Citation
“…This would imply that galaxy growth does not track the halo growth from z ∼ 2-0, so the galaxy size should be proportional to the halo's size at z ∼ 2. We find that a more detailed implementation of the standard adiabatic contraction model within a full semi-analytic merger tree model (including the effects of gas, disk instabilities, and mergers; Somerville et al in prep) produces disks that are about 50% too large at a given mass at z ∼ 0, compared with observations, but are in good agreement with the size-mass relation from CANDELS at 0.4 Brennan et al 2017). However, we do not support "pseudoevolution" as a complete explanation for two reasons.…”
Section: Theoretical Expectations For Disk Sizessupporting
confidence: 74%
“…One might expect, then, that selecting galaxies at a fixed star formation rate would select lower mass galaxies at high redshift. Furthermore, even at fixed stellar mass there is a correlation between size and SFR, such that galaxies with below-average SFR for their epoch have smaller sizes (Wuyts et al 2011;Brennan et al 2017). Finally, as noted by Behroozi et al (2013a), the inverse of the fitting formula for the average stellar mass at a given halo mass is not equivalent to the average halo mass at a given stellar mass, because of scatter in the stellarmass-halo-mass relation.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…The full galaxy population (left column) shows a strong and continuous trend of decreasing sSFR with decreasing size, at a given stellar mass in the range 10 10−11 M . However, within each of the sub-populations of quenched and (in particular) star-forming galaxies (third and second columns from the left, respectively), this trend is weaker (see also Brennan et al 2017). This implies that the trend for the full population is significantly driven by the changing proportions of these two sub-populations as a function of size at a given stellar mass: at smaller sizes, the proportion of quenched galaxies is larger.…”
Section: Comparison Discussionmentioning
confidence: 97%
“…Results from the EAGLE simulation (at z=0), on the other hand, predict a stronger dependence of galaxy size on sSFR than our higher redshift observations (Figure 2 in Furlong et al 2017), with Δlog(sSFR)/Δlog(r e ) at fixed stellar mass ranging between ∼0.6 and 1.4 compared to typical values of ∼0.1-0.5 in the observations. Using semianalytic models, Brennan et al (2017) showed a weak(er) trend among the most compact galaxies at z=0-2.5 that falls between these two extremes, although the comparison cannot be made directly as the stellar mass dependence has not been factored out. In summary, theoretical results predict a range from no residual dependence of galaxy size on SFR to moderately strong trends.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, Furlong et al (2017) did not present their higher redshift results, so that a more direct comparison at the equivalent epochs is not possible. Similarly, this information cannot be reconstructed from the results of Tacchella et al (2016) and Brennan et al (2017). Future comparisons like this between the observations and theoretical models will prove illuminating.…”
Section: Discussionmentioning
confidence: 99%